Study of the effect of varying typhoon parameters on the storm tide level in Baler Bay - Francisco, Rachel B.; Cruz, Eric C. (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
Storm tide occurences has long been present in the Philippines. Yet, it is only until the tragedy of the Typhoon Yolanda that different sectors in the country became interested on studying more about storm surge. Moreover, sites in the east coast of the Philippines are vulnerable to this hazard. In this study, the investigation on the sensitivity of the storm tide height to varying typhoon parameters is of high interest to address the problem on the lack of information about storm surge in the Philippines. Typhoon Irma (1981) was used to observe the site-specific response of the coast of Baler Bay to varying typhoon conditions i.e. Vmax and track distance. The Vmax recorded on 6-hr intervals was increased and decreased by 10% to 20%. Results show that the value of Vmax has a consistent quadratic relationship with the STL whether typhoon Irma tracks south and north. Moreover, it was noted that the south tracks produced higher STL than the north tracks under the same Vmax. The track distance of typhoon Irma was also varied by increments of 100km north and south of the bay using the original Vmax of typhoon Irma. Results show that the south tracks have a quadratic relationship with the STL while the north tracks established no clear relation with STL. Also, the highest STL was yielded by a south track 150km away from the site. This opposes the expectation that a typhoon directly hitting the site would cause higher storm tide.
Thesis (Bachelor of Science in Civil Engineering)--University of the Philippines Diliman
Keywords: Storm surges -- Baler, Philippines